Shariah Governance Practice on Indonesian Islamic Banks - Muhfiatun, Muhfiatun (Akuntabilitas, 2023)
The shariah governance system is crucial in Islamic banks because of its unique structure that is different from a conventional bank. The fundamental difference between shariah governance and conventional governance is marked by the presence of a shariah supervisory board (SSB). This study aims to analyse the practice of shariah governance in Islamic banks in Indonesia. This study uses a qualitative approach with content analysis to assess the conformity of SSB practices with applicable regulations. The results of the analysis found that there were no Islamic banks that violated the provisions in recruiting or the characteristics of SSB. This research is expected to contribute to the quality of SSB through various backgrounds.